2005
DOI: 10.1007/s00213-005-2231-5
|View full text |Cite
|
Sign up to set email alerts
|

5-HT2A/2C receptor signaling via phospholipase A2 and arachidonic acid is attenuated in mice lacking the serotonin reuptake transporter

Abstract: These results show that a lifelong elevation of the synaptic 5-HT concentration in SERT-/- mice leads to downregulation of 5-HT(2A/2C) receptor-mediated PLA2 signaling via AA and of head twitches, in response to DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 56 publications
9
50
0
Order By: Relevance
“…SERT knock-out mice have a sixfold increase in extracellular 5-HT (Bengel et al, 1998), and, in these mice, a 42% decrease is seen in the cortical but not in the striatal 5-HT 2A receptor density (Rioux et al, 1999). Consistent with this observation, pharmacological stimulation with a 5-HT 2A receptor agonist was associated with a marked attenuation of the head-twitch response and in phospholipase A2 signaling in SERT knock-out compared with SERT overexpressing mice (Qu et al, 2005). Similarly, in SERT overexpressing mice with decreased extracellular 5-HT levels, increased functional sensitivity of the 5-HT 2A receptor was found; 5-HT 2A receptor agonist stimulation induced a greater increase in both c-Fos and Arc mRNA expression in cortical brain regions and more head twitches compared with wild-type mice (Jennings et al, 2008), although the authors were unable to demonstrate significantly increased 5-HT 2A receptor binding.…”
Section: Discussionsupporting
confidence: 52%
“…SERT knock-out mice have a sixfold increase in extracellular 5-HT (Bengel et al, 1998), and, in these mice, a 42% decrease is seen in the cortical but not in the striatal 5-HT 2A receptor density (Rioux et al, 1999). Consistent with this observation, pharmacological stimulation with a 5-HT 2A receptor agonist was associated with a marked attenuation of the head-twitch response and in phospholipase A2 signaling in SERT knock-out compared with SERT overexpressing mice (Qu et al, 2005). Similarly, in SERT overexpressing mice with decreased extracellular 5-HT levels, increased functional sensitivity of the 5-HT 2A receptor was found; 5-HT 2A receptor agonist stimulation induced a greater increase in both c-Fos and Arc mRNA expression in cortical brain regions and more head twitches compared with wild-type mice (Jennings et al, 2008), although the authors were unable to demonstrate significantly increased 5-HT 2A receptor binding.…”
Section: Discussionsupporting
confidence: 52%
“…The authors cite five earlier studies (Table 7 in Dougherty and Aloyo, 2011) that all reported similar findings, in which changes in 5-HT 2A receptor density were correlated with changes in the number of HTRs. Qu et al (2005) used PLA 2 as a measure of regional brain activation in SERT KO mice (SERT 2/2 ) and their 316 Nichols littermate controls (WT; SERT +/+ ). Unanesthetized mice were injected intravenously with [ 3 H]AA and the regional coefficient of incorporation k* of AA from plasma into phospholipids of individual brain regions was subsequently measured by quantitative autoradiography in 71 different brain regions.…”
Section: B Mouse Modelsmentioning
confidence: 99%
“…27,28 As antagonism to 5-HT2A receptors 29,30 increases adiponectin levels, this chain of events may protect obese 5-HTT mice from the full metabolic syndrome. Although the limitations of germline ko models compared with inducible ko strategies have to be considered, 5-HTT ko mice differ from previously described models of late-onset obesity and may serve as a paradigm for a different subset of obese humans.…”
Section: Discussionmentioning
confidence: 99%